Gut Faecalibacterium abundance in patients with plasma cell disorders is associated with survival after autologous HSCT - Erin A. Dean; Arkaprava Roy; Rick Y. Lin; Raad Z. Gharaibeh; Derek M. Li; Josee Gauthier; Christian Jobin; John R. Wingard (Blood Neoplasia)
Abstract: The gut microbiota (GM) has been linked to the development, progression, and response to therapy in plasma cell neoplasms (PCNs). The primary goal of this study was to investigate the relationship between the composition of the GM before and during autologous hematopoietic stem cell transplant (HSCT) with clinical outcomes of patients with PCNs. We focused on the genus Faecalibacterium, which includes the most abundant anaerobic commensal bacterium in the GM. Fecal samples were collected prospectively before, mid (at 1 week from the start of intervention), and end (at engraftment) of intervention (liberalized vs neutropenic diet) and subjected to 16S ribosomal DNA sequencing. Eighty-three patients were enrolled. Their median age was 64 (range, 31-79) years. Fifty-four patients received HSCT as part of frontline therapy and 29 for relapsed/refractory disease. With median follow-up time for survivors (n = 82) of 32 (range, 0.7-61) months, the median progression-free survival (PFS) was 40 months. Higher preintervention Faecalibacterium abundance was associated with improved PFS (hazard ratio [HR], 0.92; 95% confidence interval [CI], 0.86-0.99; P = .02). Faecalibacterium abundance was found to decrease early after transplant (P < .01). Although the administration of high-dose melphalan (200 mg/m2) was significantly associated with PFS in both univariable (HR, 0.38, 95% CI, 0.19-0.75; P = .006) and multivariable (HR, 0.42; 95% CI, 0.20-0.87; P = .02) analyses, preintervention Faecalibacterium abundance remained independently associated with PFS (HR, 0.93; 95% CI, 0.86-0.99; P = .04) on multivariable analysis. In conclusion, lower preintervention Faecalibacterium abundance was associated with inferior PFS.